Analisis Perbandingan Persepsi Konsumen Terhadap Minat Beli Pada Giant A.Yani Dan Hypermart Royal Plaza Surabaya - Sugiono, Ilyas; Tjahjono, Endro; Novaria, Rachmawati (Jurnal Dinamika Administrasi Bisnis, 2017)
This study entitled "Comparative Analysis Of Consumer Perception Of Interest To Buy On Giant A. Yani And Hypermart Royal Plaza Surabaya". This study aims to determine is there a difference in consumers 'perception of buying interest and to find out how much difference the consumers' perception of buying interest Giant Hypermart A. Yani and Royal Plaza Surabaya. The population in this study were people who shopped at Giant or Hypermart A. Yani Royal Plaza Surabaya in the period November 2016 until December 2016.         The sampling method used was purposive sampling with the number of respondents as many as 100 people. Variables used, as many as five variables, among others: price, place, product, promotion, and buying interest. The analysis tool used is independet sample t test.    The results showed that the difference in consumers' perception of price, place, product, promotion, and buying interest among Giant Hypermart.  Keywords: Difference, perception, consumer and retail.